Unsung Muslim Women Warriors of 1857: The First War of Independence in India - Razia Sultana (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2026)
The revolt of 1857 which is called the first war of independence is a foundational stone in the anti- colonial history of the subcontinent of India. However, the existing historiography primarily highlights the participation of male leaders and their military engagement, it does not sufficiently explore women's role and their multifaceted participation and specially Muslim women’s sacrifices recognised rarely. This paper describes the role of Muslim women in the First War of Independence of 1857 as political leaders, military participants, organisers, motivators, and martyrs. Muslim women belonging to different social backgrounds, such as royal households, aristocratic families, the middle class, and marginalised groups, and living in diverse regions made significant contributions to the resistance against the British.Their involvement was not only symbolic support, but they also directly participated in governance, battlefield engagements, troop mobilization, intelligence gathering, and logistical coordination. This paper exposes the sacrifices of Muslim women, which have been ignored over time and not mentioned by most historians. The study seeks to restore women to their rightful place in the historical understanding of the 1857 uprising and to highlight their enduring legacy in the history of resistance and freedom.